TERAPI PREDNISON MEMBERIKAN LUARAN KLINIS YANG BAIK PADA MIOSITIS POST VAKSINASI - Ivan Santosa; Yudy Goysal; Andi Kurnia Bintang; Cahyono Kaelan (NEURONA, 2021)
A six-year-old girl was consulted from the Pediatrics department to the Neurology outpatient clinic at Wahidin Sudirohusodo Hospital in Makassar with an initial diagnosis of neuropathy. She complained of weakness on both legs suffered a month before treatment, she had difficulty reaching a standing position from sitting or squatting. She walked quite normally when standing, there was no disturbance in gait, but she had difficulty on climbing stairs, and had myalgia in the leg area. There was a history of intramuscular injection of diphtheria tetanus (Td) vaccine in the right upper arm. She got the vaccine according to the vaccination program. On physical examination, vital signs were within normal limits, there was slight paraparesis, decreased patellar reflex and no pathological reflexes. Sensory and autonomic physical examination were normal. There was Gower’s sign noted. Laboratory investigations findings: SGOT 134, SGPT 49, LDH 1584, CK 1922.80. Biopsy finding shows inflammatory changes consistent with myositis. Prednisone therapy provides significant clinical improvement. Keywords: Myositis, prednisone, vaccination